Aktualisasi Etika Guru dan Murid Al-‘Āmili di Era Disrupsi - Ahmad Muntakhib; Fatah Syukur; Syamsul Ma'arif; Musthofa Musthofa (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
The development of the era that resulted in to an era of disruption encourages changes in educational activities. It triggers new problems in educational ethics, including the ethics of teachers and students. The ethical constructions of teachers and students that have been formulated by scholars and education experts are by the conditions of their time. One of the scholars who laid the foundations for teachers and students' ethics was Zainuddin bin Nuruddin 'Ali bin Ahmad Al-'Amili Al-Juba'i or also known as Al-'Amili. This study aims to interpret the actualization of the ethics of teachers and students of Al-'Amili in the context of the era of disruption. This research was conducted with a qualitative approach, namely the library research method with the primary data source of the book Munyah al-Murīd fī Adab al-Mufīd wa al-Mustafīd by Al-'Amili. The analysis was performed using Content Analysis techniques. This study found that teacher and student ethics can apply in general, namely that teachers and students have their own ethics in the educational process. The thought of Al-'Amili is universal so that it can be actualized in the present. In an era of disruption where values are uprooted and replaced by new values, the role of ethics becomes important to underlie teachers' and students' activities in learning. One of them is the ethical model of the relationship between teacher and student as an educational relationship that is Sufistic by highlighting the characteristics of holiness in learning.